Experiences with EPAs, potential benefits and pitfalls. (August 2014) - van Loon, Karsten A.; Driessen, Erik W.; Teunissen, Pim W.; Scheele, Fedde
Abstract: Reforms in postgraduate medical education (PGME) exposed a gap between educational theory and clinical practice. Entrustable Professional Activities (EPAs) were introduced to assist clinicians in bridging this gap and to create better consonance between the intended and the enacted curriculum. In this viewpoint paper, we discuss the potential and the pitfalls of using EPAs in PGME. EPAs promise an effective way of teaching abstract competencies in a curriculum based on real-life professional activities that are suitable for clinical assessment. Summative judgement is used to entrust a resident step by step in a certain EPA, resulting in an increase of independent practice. However, we argue that the success of EPAs depends on (1) a balance: brief focussed descriptions against the requirements for detail and (2) a precondition: a mature and flexible workplace for learning.